Diabetic wound healing in a MMP9‐/‐ mouse model. Issue 5 (19th July 2016) - Cho, Hongkwan; Balaji, Swathi; Hone, Natalie L.; Moles, Chad M.; Sheikh, Abdul Q.; Crombleholme, Timothy M.; Keswani, Sundeep G.; Narmoneva, Daria A.
ABSTRACT: Reduced mobilization of endothelial progenitor cells (EPCs) from the bone marrow (BM) and impaired EPC recruitment into the wound represent a fundamental deficiency in the chronic ulcers. However, mechanistic understanding of the role of BM‐derived EPCs in cutaneous wound neovascularization and healing remains incomplete, which impedes development of EPC‐based wound healing therapies. The objective of this study was to determine the role of EPCs in wound neovascularization and healing both under normal conditions and using single deficiency (EPC) or double‐deficiency (EPC + diabetes) models of wound healing. MMP9 knockout (MMP9 KO) mouse model was utilized, where impaired EPC mobilization can be rescued by stem cell factor (SCF). The hypotheses were: (1) MMP9 KO mice exhibit impaired wound neovascularization and healing, which are further exacerbated with diabetes; (2) these impairments can be rescued by SCF administration. Full‐thickness excisional wounds with silicone splints to minimize contraction were created on MMP9 KO mice with/without streptozotocin‐induced diabetes in the presence or absence of tail‐vein injected SCF. Wound morphology, vascularization, inflammation, and EPC mobilization and recruitment were quantified at day 7 postwounding. Results demonstrate no difference in wound closure and granulation tissue area between any groups. MMP9 deficiency significantly impairs wound neovascularization, increases inflammation, decreases collagen deposition, and decreases peripheral blood EPC (pb‐EPC) counts when compared with wild‐type (WT). Diabetes further increases inflammation, but does not cause further impairment in vascularization, as compared with MMP9 KO group. SCF improves neovascularization and increases EPCs to WT levels (both nondiabetic and diabetic MMP9 KO groups), while exacerbating inflammation in all groups. SCF rescues EPC‐deficiency and impaired wound neovascularization in both diabetic and nondiabetic MMP9 KO mice. Overall, the results demonstrate that BM‐derived EPCs play a significant role during wound neovascularization and that the SCF‐based therapy with controlled inflammation could be a viable approach to enhance healing in chronic diabetic wounds.